Perbandingan Efektivitas Evaluasi Hasil Belajar Peserta Didik Melalui Quizizz dan Google Form pada Materi Pemetaan, Penginderaan Jauh dan SIG Kelas XII IPS di SMAN Mojogedang Tahun Ajaran 2021/2022 - Dilla Ridilla Falestina Hartadi (Universitas Sebelas Maret (UNS), 2023)
The aims of this study was: (1) Knowing the differences in geography learning outcomes between the use of Quizizz and Google Form for class XII Social Studies at SMAN Mojogedang for the academic year 2021/2022.This research raises material about Mapping, Remote Sensing, and GIS. This type of research is a quasi-experimental research with Posttest Only Design. The population in this study were 5 classes with 166 students. Sampling was done by cluster random sampling, the sample in this study amounted to 67 students consisting of 33 students for the experimental class and 34 students for the control class. The instrument used is a posttest learning outcome test which consists of 25 questions.The results of data analysis showed that the average score of the experimental class students' learning outcomes was 84 and the control class students' average scores were 80.23. The results of hypothesis testing using t test, where the calculation results obtained t count > t table that is 2.013 > 1.668. From the results of the analysis, it was found that there were differences in geography learning outcomes between students who used Quizizz as a learning evaluation tool and students who used Google Form.Keywords: Quizizz, Google Form, learning outcomes